The Effect of Anterior Cruciate Ligament Deficiency and Reconstruction on the Patellofemoral Joint - de Velde, Samuel K. Van (2008)
BACKGROUND: Little is known about the effect of anterior cruciate ligament deficiency and reconstruction on the patellofemoral joint. HYPOTHESIS: Anterior cruciate ligament deficiency changes the patellofemoral joint biomechanics. Reconstruction of the ligament does not restore the altered patellofemoral joint function. STUDY DESIGN: Controlled laboratory study. METHODS: Eight patients with an acute anterior cruciate ligament injury in 1 knee and the contralateral side intact were included in the study. Magnetic resonance and dual-orthogonal fluoroscopic imaging techniques were used to compare the patellofemoral joint function during a single-leg lunge between the intact, the anterior cruciate ligament–injured, and the anterior cruciate ligament–reconstructed knee. Data on the patellar tendon apparent elongation and orientation, patellar tracking, and patellofemoral cartilage contact location were collected preoperatively and at 6 months after reconstruction. RESULTS: Anterior cruciate ligament deficiency caused a significant apparent elongation and change in orientation of the patellar tendon. It decreased the flexion and increased the valgus rotation and tilt of the patella. Anterior cruciate ligament injury caused a proximal and lateral shift in patellofemoral cartilage contact location. Anterior cruciate ligament reconstruction reduced the abnormal apparent elongation but not the orientation of the patellar tendon, and it restored the patellar flexion and proximal shift in contact. The abnormal patellar rotation, tilt, and lateral shift in cartilage contact persisted after reconstruction. CONCLUSION: The altered function of the patellar tendon in anterior cruciate ligament deficiency resulted in an altered patellar tracking and patellofemoral cartilage contact. Persistent changes in patellofemoral joint function after anterior cruciate ligament reconstruction imply that reconstruction of the anterior cruciate ligament does not restore the normal function of the patellofemoral joint. CLINICAL RELEVANCE: The abnormal kinematics of the patellofemoral joint might predispose the patellofemoral cartilage to degenerative changes associated with anterior cruciate ligament deficiency, even if the ligament is reconstructed in a way that restores anteroposterior knee laxity.